Pengukuran Kinerja Rumah Sakit Umum Pusat dr. Soeradji Tirtonegoro Klaten dengan Metode Balanced Scorecard Perspektif Bisnis Internal dan Pembelajaran dan Pertumbuhan - Siti Kurnia Widi Hastuti; Ratu Bela Sakti (International Journal of Healthcare Research, 2020)
Central General Hospital dr. Soeradji Tirtonegoro Klaten is a type A hospital an as a referral center hospital. This hospital is required to be able to provide health services in accordance with the standard. During this time the hospital used performance measurement that have been set by the government, measuring performance from the financial aspect alone is not enough so it is also necessary from the non-financial aspects. Performance measurement using the Balanced Scorecard is the right solution because performance measurement is seen from various aspects namely financial and non-financial aspects namely financial and non-financial aspects. This study aims to determine the performance of the central general hospital dr. Soeradji Tirtonegoro Klaten Internal Business Perspective and Learning and Growth Perspective. This study used a qualitative method with phenomenological research design. The research subjects consisted of the head of the HR sub- division, the head of the medical services monitoring and evaluation section, the medical record installation reporting staff, the head of the training and education sub-office, the employee and a sample of 92 employees consisting of medical and non-medical personnel. The result of performance measurements conducted at the Central General Hospital dr. Soeradji Tirtonegoro Klaten used the Balanced Scorecard method of internal business perspective and learning and growth obtained a score of 0 which means good enough. Performance measurement Of The Central General Hospital, dr. Soeradji Tirtonegoro Klaten With the Balanced Scorecard Method viewed from an internal business perspective and Learning and Growth is said to be “Good Enough”